Tilianin suppresses NLRP3 inflammasome activation in myocardial ischemia/reperfusion injury via inhibition of TLR4/NF-κB and NEK7/NLRP3 - Suyue Yin; Kaixi Han; Di Wu; Zihan Wang; Ruifang Zheng; Lianhua Fang; Shoubao Wang; Jianguo Xing; Guanhua Du (Frontiers Media S.A., 2024)
Tilianin, a flavonoid compound derived from Dracocephalum moldavica L., is recognized for its diverse biological functionalities, in particular alleviating myocardial ischemia-reperfusion injury (MIRI). There is ample evidence suggesting that the NLRP3 inflammasome has a significant impact on the development of MIRI. In this study, rats undergoing the ligation and subsequent release of the left anterior descending (LAD) coronary artery and H9c2 cardiomyocytes subjected to oxygen-glucose deprivation/reoxygenation (OGD/R) were used to investigate the effects of tilianin on NLRP3 inflammasome and its anti-MIRI mechanisms. Upon reperfusion, the rats were intraperitoneally injected with tilianin at doses of 3, 10, 30 mg/kg. H9c2 cells were treated with tilianin at concentrations of 10, 30, and 50 μg/mL. Echocardiography, TTC staining and TUNEL staining demonstrated that tilianin remarkably improved cardiac function and mitigated myocardial damage in MIRI rats. Additionally, notable inflammatory response reduction by tilianin was evidenced by subsequent hematatoxylin-eosin (HE) staining, inflammatory cytokines assay, and quantitative proteomics. Further western blotting analysis and immunofluorescence staining showed tilianin decreased the levels of TLR4, p-NF-κB, NLRP3, and ASC in MIRI rats and H9c2 cells exposed to OGD/R, alongside a significant reduction in cleaved gasdermin D, mature IL-1β and IL-18. Molecular docking, cellular thermal shift assay (CETSA) and co-immunoprecipitation (co-IP) assay revealed that tilianin impeded the interaction between NLRP3 and NEK7. Taken together, tilianin protects cardiomyocytes from MIRI by suppressing NLRP3 inflammasome through the inhibition of the TLR4/NF-κB signaling pathway and the disruption of the NEK7/NLRP3 interface. These findings underscore the potential of tilianin as a promising therapeutic candidate for MIRI.